Production, Partial Purification and Characterization of Protease through Response Surface Methodology by Bacillus subtilis K-5 - Shad, Aqeel Ahmed; Ahmad, Tanveer; Iqbal, Muhammad Farooq; Asad, Muhammad Javaid; Nazir, Sidrah; Mahmood, Raja Tahir; Wajeeha, Amtul Wadood (Brazilian Archives of Biology and Technology, 2024)
Abstract The aim of present study was the production of protease from local Bacillus subtilis through solid state fermentation. Response Surface Methodology (RSM) was used for the optimization of all the culture conditions. Casein (1% w/v) was used as a substrate in nutrient agar medium for the screening of enzyme production potential and showed maximum zone of clearance (4.6 cm). It was identified as Bacillus subtilis K-5 by genetic identification based on 16S rRNA and blast technology of NCBI. Among culture conditions, incubation temperature, incubation time, pH of the medium and moisture level of the substrate were optimized. Maximum protease production was observed at 37oC, pH 9.0 with incubation time of 36 h and moisture to substrate ratio of 1: 0.75. Maximum protease production of 70.21 U/mL was recorded when wheat bran was used as an agro-industrial substrate. The activity of crude protease was observed 99.63 % at 60oC and pH 10.0 with protein concentration 0.63 mg/mL and specific activity of 111.56 U/mg. Protein contents of 0.57 mg/mL (specific activity of 124.72 U/mg) and protein contents of 0.44 mg/mL (specific activity of 143.65 U/mg) were observed by 70% saturation with ammonium sulphate and gel chromatography, respectively. Line Weaver Burk plot was used to find its Vmax and Km, which were 344. 83 mg/mL/min and 100.04 mg/mL, respectively. The study concluded that Bacillus subtilis K-5 is thermophilic and alkaliphilic strain which produces active protease and can be used as potential microorganism for industries.